Conclusion: Same As it Ever Was? (2013)
Th is book has attempted to look at the framing and representation of suburbia by popular cultural texts including literary, onscreen and aural forms in order to draw some conclusions about suburbs from the multiplicity of depictions discussed. If suburbia has been the subject under the microscope then popular culture is the lens through which it has been viewed. Mass popular culture aft er all can be a catalyst for cultural incorporation and given that suburbia is a concept that eludes easy defi nition, its reproduction in popular culture has helped to shape the concept in the popular imagination. Uniting all of the phenomena discussed is an ostensible desire to entertain the masses. Th e book has attempted to come up to date from the imagery of the Gray Flannel Suit and Pooter. A fuller account than space allows for here would consider other cultural forms or broader structural factors of socio-political change in suburbia but for now it can be said that the popular cultures discussed need to be located in context (i) alongside other competing media and culture, for example news reporting which commands sometime separate and sometimes overlapping audiences and (ii) against the backdrop of wider societal trends. Some of the cultural forms dealt with have distinctive conventions of genre and common plot devices (e.g. the sitcom) whereas others less obviously have categorical logics to them (e.g. popular music which covers sonically diff erent styles, e.g. grime and Britpop).